Islamic Inheritance Law as Living Law in South Sulawesi: Developing a Contextual-Moderate Receptie Approach - Muhammad Fajri; Idzam Fautanu; Ramdani Wahyu Sururie; Enceng Arif Faizal; Taufik, Muh. Bambang (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines Islamic inheritance practices among Muslim communities in South Sulawesi, where Qur’anic inheritance norms interact with local traditions and family-based mechanisms of property transfer within a living law framework. Although Islamic inheritance law is normatively ijbārī and grounded in definitive Qur’anic texts, empirical practices frequently involve lifetime gifts (hibah), bequests (wasiat), family deliberation, caregiving-based considerations, and consensual redistribution. Employing a normative-empirical juridical method with a socio-legal approach, this study draws on document analysis and in-depth interviews with Religious Court judges, religious officials, customary leaders, and community figures across several regions of South Sulawesi. The findings reveal that Islamic inheritance law remains widely acknowledged as a binding religious obligation rooted in faith commitment, yet its application is commonly mediated through classical Islamic legal mechanisms rather than routine formal adjudication. These practices do not function as attempts to evade inheritance law, but as context-sensitive applications aimed at preserving justice, family harmony, and social legitimacy within Islamic law as living law. However, the prevalence of unregulated legal eclecticism exposes a risk of normative dilution when definitive Qur’anic inheritance norms are treated as negotiable preferences. In response, this study advances a contextual-moderate receptie approach, grounded in Islamic legal principles and maqāṣid-based systems thinking, to balance normative certainty with contextual justice. By positioning Islamic inheritance law as the normative core of an integrated family property transfer system encompassing waris, hibah, and wasiat, this study contributes to socio-legal scholarship on Islamic law and legal pluralism within Indonesia’s plural legal landscape.